Caffeine decreases exhaled nitric oxide. Issue 4 (1st April 2002) - Bruce, C; Yates, D H; Thomas, P S
Abstract : Background: Caffeine is known to inhibit phosphodiesterases, to mobilise intracellular calcium, and to act as an antagonist at adenosine receptors, all of which can potentially alter nitric oxide (NO) production. It was therefore hypothesised that caffeine may alter exhaled NO (eNO) levels. Methods: In a randomised, single blind, crossover manner, 12 normal subjects consumed either (1) coffee and a placebo capsule, (2) decaffeinated coffee and a capsule of 200 mg caffeine, or (3) decaffeinated coffee and a placebo capsule. Serum caffeine levels were measured at baseline and 1 hour later. Exhaled NO levels were also measured at baseline and each hour for 4 hours. Results: A significant percentage fall in mean (SE) eNO from baseline was seen 1 hour after either caffeinated coffee or a caffeine capsule when compared with placebo (13.5 (4.0)%, p=0.009 and 19.0 (3.8)%, p=0.001, respectively). Conclusion: Caffeine causes a significant decrease in eNO which will need to be considered when designing trials to measure eNO levels. The mechanism may be via adenosine receptor antagonism or by altering levels of cGMP.